Critical Thinking Skills and Digital Literacy of High School Students in Science Learning Using E-Learning with STEM Vision - Rahayu, Sarini; Isnaeni, Wiwi; Masturi, Masturi (Journal of Innovative Science Education, 2022)
Critical thinking skills and digital literacy are competencies that students must have in facing the challenges of 21st century learning, including contextual biology learning and a STEM approach. The learning process is accompanied by technological developments so that it needs to be utilized optimally through E-Learning. This study aims to analyze the effect of STEM-Vision E-Learning on digital literacy, critical thinking, and determine teacher and student responses to the application of STEM-Vision E-Learning learning. This study used a quasi-experimental design with a pretest-posttest control group design. The subjects of this study included 60 students in class XI MIPA 4 and 5 as the Experiment class (E-Learning with STEM Vision) and 60 students in XI MIPA 6 and 7 as the control class (Conventional E-Learning). This research was conducted at SMA N 1 Ungaran. The data measured in this study were critical thinking skills, digital literacy, and teacher and student responses to the application of STEM-Vision E-Learning learning. This study uses measuring instruments of observation, interviews, questionnaires, written tests and analyzed using reliability test, validity test, n-gain test. The results showed that in general there was a significant difference in digital literacy between the experimental class and the control class, In addition, there is a significant difference in critical thinking skills between the experimental class and the control class and there is a significant difference in critical thinking skills and digital literacy between the experimental class and the control class. Learning STEM Vision E-Learning can be implemented well, students and teachers give a positive response to learning STEM Vision E-Learning on the material circulation system. Suggestions in this study need a STEM approach between teachers and students so that online learning takes place without obstacles.